Exploring Impact of Multidisciplinary Care on Patient Activation in Saudi Rheumatoid Arthritis Patients: A Cross-Sectional Survey—Extended Results from the COPARA National Project - Almalag,Haya; Al Juffali,Lobna; Alshehri,Maha; Altokhais,Nouf; Aljanobi,Ghada; El Dessougi,Maha; AlHarthi,Amal; Attar,Suzan; Bahlas,Sami; Alfurayj,Abdullah; Alazmi,Mansour; Asiri,Alhussain; et al. (Journal of Multidisciplinary Healthcare, 2023)
Haya M Almalag,1 Lobna Al Juffali,1 Maha M Alshehri,2 Nouf A Altokhais,2 Ghada A Aljanobi,3 Maha I El Dessougi,4 Amal AlHarthi,4 Suzan M Attar,5 Sami M Bahlas,5 Abdullah S Alfurayj,6 Mansour S Alazmi,7 Alhussain M Asiri,8 Mohammed M AlOmair,8 Mohammed A Omair9 1Department of Clinical Pharmacy, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 2College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 3Rheumatology Unit, Department of Medicine, Johns Hopkins Aramco Healthcare, Dhahran, Saudi Arabia; 4Rheumatology Unit, Department of Medicine, Security Forces Hospital, Riyadh, Saudi Arabia; 5Rheumatology Unit, Department of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 6Rheumatology Unit, Department of Medicine, Buraidah Central Hospital, Buraidah, Saudi Arabia; 7Rheumatology Unit, Department of Medicine, Prince Mohammed Medical City, Sakaka-Aljouf, Saudi Arabia; 8Rheumatology Unit, Department of Medicine, Aseer Central Hospital, Abha, Saudi Arabia; 9Rheumatology Unit, Department of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Haya M Almalag, Department of Clinical Pharmacy, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia, Email halmalaq@ksu.edu.saIntroduction: Multidisciplinary setting in healthcare provide positive patient outcomes.Objective: To evaluate the impact of specialized rheumatology clinics (multidisciplinary settings) on the activation and engagement of rheumatoid arthritis (RA) patients.Material and Methods: This cross-sectional survey assessed patient activation using the patient activation measure-13. Participants attending Specialized Rheumatology Clinics (SRC multidisciplinary clinics) were compared with age- and sex-matched patients attending Standard of Care (SOC). The study was observational in nature, assessing several demographic and therapeutic options and their relation to the clinical setting and patient activation.Results: This study included 117 SRC matched RA patients with 117 SOC. The majority of the included ...